Anti-neuroinflammatory activities of indole alkaloids from kanjang (Korean fermented soy source) in lipopolysaccharide-induced BV2 microglial cells. (15th December 2016) - Kim, Dong-Cheol; Quang, Tran Hong; Yoon, Chi-Su; Ngan, Nguyen Thi Thanh; Lim, Seong-Il; Lee, So-Young; Kim, Youn-Chul; Oh, Hyuncheol
Highlights: Seven indole alkaloid derivatives were isolated from kanjang (Korean soy source). These metabolites exhibited potent inhibitory effects on LPS-induced NO and PGE2 production in BV2 cells. The expressions of iNOS, COX-2, and pro-inflammatory cytokines were also repressed in LPS-induced BV2 cells. Down-regulation of NF-κB and p38 MAPK pathways was involved in the anti-neuroinflammatory effects of these metabolites. Abstract: Kanjang (Korean soy sauce) is a byproduct of the production of the Korean fermented soybean. In the present study, seven indole alkaloid derivatives were isolated from methanol extract of kanjang. Their structures were identified as 1-propyl-1, 2, 3, 4-tetrahydro-β-carboline-3-carboxylic acid (1 ), 1-methyl-1, 2, 3, 4-tetrahydro-β-carboline-3-carboxylic acid (2 ), 1-methyl-1, 2, 3, 4-tetrahydro-β-carboline-1-carboxylic acid (3 ), 3-indoleacetic acid (4 ), Nb -acetyltryptamine (5 ), 1-methyl-3, 4-dihydro-β-carboline (6 ), and flazine (7 ) by NMR and MS analyses. Preliminary screening for anti-neuroinflammatory effects of isolated indole alkaloids in lipopolysaccharide (LPS)-stimulated BV2 cells revealed that these compounds inhibited the production of nitric oxide and prostaglandin E2 . For the subsequent investigation of anti-neuroinflammatory action of these metabolites, compounds4 and7 were selected, and the results revealed that these inhibitory effects correlated with the suppressive effect of4 and7 on inducible nitric oxide synthase and cyclooxygenase-2 expression in LPS-stimulated BV2 cells. In regards to the mechanism of the anti-inflammatory effect, 4 and7 significantly inhibited the nuclear factor-kappa B pathway.